Traditional Chinese Medicine nursing of chronic pelvic inflammatory disease (慢性盆腔炎的中医护理) - YANG Fei (杨菲); GENG Qingwen (耿庆文); WANG Yali (王亚丽); TANG Ling (唐玲); REN Mei (任梅) (Association of Integrative Nursing, 2021)
This paper summarized the etiology and pathogenesis of chronic pelvic inflammatory disease in Traditional Chinese Medicine (TCM), TCM formula, diet and nutrition guidance and oral care. The targeted TCM nursing interventions by syndrome differentiation were carried out, helping to relieve disease-associated symptoms and pain, and achieving better patient compliance with treatment. (本文从慢性盆腔炎的中医病因病机、中药组方、饮食指导、中药口服护理等方面进行了总结, 通过辨证用药, 实施针对性的中医护理干预, 有助于改善慢性盆腔炎患者的临床症状, 缓解疼痛, 且患者更易于接受。)